Non-Toxic Fractions of Hypericum perforatum and Hypericum oblongifolium Inhibit Protein Glycation, Free Radicals Production and Lipid Peroxidation in vitro - GHULAM ABBAS,; M. Jawad Hassan,; Zeb Saddiqe,; Muhammad Shahzad,; Javid Hussain,; Shahida Parveen,; Alya Maimoona, (International Journal of Phytomedicine, 2013)
In this study, the biological activities of the crude extracts/fractions of two medicinally important plants Hypericum perforatum and Hypericum oblongifolium were investigated for their potential antiglycation, antioxidant, anti lipid peroxidation and cytotoxicity studies. In antioxidant 1,l-Diphenyl-2-picryIhydrazylradical (DPPH) assay, aqueous and n-Butanol fractions of H. perforatum exhibited significant antioxidant potential with IC50 values 91.443±2.052 and 119.781±2.821 µg/mL respectively while n-Butanol fraction of H. oblongifolium also showed moderate activity with IC50 value 215.375±3.562 µg/mL. The n-Butanol fraction of H. perforatum showed 63.466% activity and aqueous fraction showed 52.901% inhibition in lipid per oxidation assay while H. oblongifolium fractions, dichloromethane, methanol and n-Butanol exhibited 67.206%, 61.874% and 54.219% inhibition, respectively. The n-Butanol and n-hexane fractions showed 57.250% and 50.018% inhibitory activity against protein glycation. All fractions from both species were found to be non-toxic largely in cytotoxicity assay except for n-hexane fraction of H. perforatum and dichloromethane fraction of H. oblongifolium which showed mild cytotoxicity with IC50 values of 21.70±0.237 µg/mL and 26.612±0.014 µg/mL respectively as compared to cycloheximide used as standard (IC50 = 0.073±0.1 µg/mL). The study concluded that the aqueous and n-Butanol fractions of both the species possess promising antioxidant, antiglycation and anti lipid per oxidation activities with no toxic effects in vitro.